Angiotensin Receptor 1 Blockers Prolong Time to Recurrence after Radiofrequency Ablation in Hepatocellular Carcinoma patients: A Retrospective Study - Antonio Facciorusso; Mohamed A. Abd El Aziz; Ivan Cincione; Ugo Vittorio Cea; Alessandro Germini; Stefano Granieri; Christian Cotsoglou; Rodolfo Sacco (Biomedicines, 2020)
Inhibition of angiotensin II synthesis seems to decrease hepatocellular carcinoma recurrence after radical therapies; however, data on the adjuvant role of angiotensin II receptor 1 blockers (sartans) are still lacking. Aim of the study was to evaluate whether sartans delay time to recurrence and prolong overall survival in hepatocellular carcinoma patients after radiofrequency ablation. Data on 215 patients were reviewed. The study population was classified into three groups: 113 (52.5%) patients who received neither angiotensin-converting enzyme inhibitors nor sartans (group 1), 59 (27.4%) patients treated with angiotensin-converting enzyme inhibitors (group 2) and 43 (20.1%) patients treated with sartans (group 3). Survival outcomes were analyzed using Kaplan–Meier analysis and compared with log-rank test. In the whole study population, 85.6% of patients were in Child-Pugh A-class and 89.6% in Barcelona Clinic Liver Cancer A stage. Median maximum tumor diameter was 30 mm (10–40 mm) and alpha-fetoprotein was 25 (1.1–2100) IU/mL. No differences in baseline characteristics among the three groups were reported. Median overall survival was 48 months (42–51) in group 1, 51 months (42–88) in group 2, and 63 months (51–84) in group 3 (p = 0.15). Child-Pugh stage and Model for End-staging Liver Disease (MELD) score resulted as significant predictors of overall survival in multivariate analysis. Median time to recurrence was 33 months (24–35) in group 1, 41 (23–72) in group 2 and 51 months (42–88) in group 3 (p = 0.001). Number of nodules and anti-angiotensin treatment were confirmed as significant predictors of time to recurrence in multivariate analysis. Sartans significantly improved time to recurrence after radiofrequency ablation in hepatocellular carcinoma patients but did not improve overall survival.